Metafora dalam Kumpulan Puisi “Sindikat Lara’’ Karya Ricardus Asbanu (Metafora Lakoff dan Johnson) - Jimron Tamonob; Marselus Robot; Margareta P.E Djokaho (YASIN, 2026)
Although metaphors are widely used in Ricardus Asbanu’s poetry collection Sindikat Lara to represent various life experiences through figurative language, their forms and meanings have not been extensively examined based on George Lakoff and Mark Johnson’s conceptual metaphor theory. This study aims to describe the forms and meanings of the metaphors contained in the poetry collection. This study employed a qualitative descriptive method, with the book Sindikat Lara serving as the data source, while the research data consisted of words, phrases, clauses, and sentences containing metaphors. The data were collected through library research, reading, and note-taking techniques and were subsequently analyzed by identifying and classifying them based on Lakoff and Johnson’s conceptual metaphor theory. The findings from the analysis of five poems, namely Catatan Kaki, Jum’at Agung, Obrolan Air Mata, Ikhlas di Titik Terakhir, and Rindu Paling Sakral, reveal three types of conceptual metaphors: structural, orientational, and ontological metaphors. These three types of metaphors are interrelated in constructing the meanings of the poems by representing emotional experiences, social relationships, and spiritual reflections, as well as concretizing various abstract concepts, such as pain, longing, love, hope, and sadness. This study concludes that metaphors play an important role in constructing meaning, strengthening emotional expression, and reflecting the poet’s life experiences. These findings contribute to the development of literary studies and cognitive linguistics, enrich the teaching of poetry appreciation, and serve as a reference for further research on metaphors using different objects and approaches.